A streetcar named desire based on the original play "A streetcar named desire" by Tenessee Williams, presented on the stage by Irene Meyer Selznick ; original director's version - Williams, Tennessee 1911-1983; North, Alex 1910-1991 (Warner Home Video, 1997)
An uncensored version of the story of a repressed widow who visits her sister in New Orleans and is raped and driven mad by her brother-in-law.
Orig.: USA 1951
Keywords: Feature films; Films for the hearing impaired; Lust -- Drama; Man-woman relationships -- Drama; New Orleans (La.) -- Drama; Videos (DVD)